Synthesis of a benzene-annulated analogue of resolving E1 and other lipid mediators - Lombardo, Daniel Mario (Curtin University, 2015)
The resolvins are a class of short-lived, naturally occurring compounds with potent anti-inflammatory effects. Using a sequential Sonogashira-Stille reaction, the formal total synthesis of resolvin E1 and the synthesis of a benzene annulated analogue of this compound were completed. The fusion of the benzene ring improves the stability and retains the molecules activity towards the BLT-1 receptor.